Direct observation of the collapse of the delocalized excess electron in water - Savolainen, Janne; Uhlig, Frank; Ahmed, Saima; Hamm, Peter; Jungwirth, Pavel (Nature chemistry, 2014)
It is generally assumed that the hydrated electron occupies a quasi-spherical cavity surrounded by only a few water molecules in its equilibrated state. However, in the very moment of its generation, before water has had time to respond to the extra charge, it is expected to be significantly larger in size. According to a particle-in-a-box picture, the frequency of its absorption spectrum is a sensitive measure of the initial size of the electronic wavefunction. Here, using transient terahertz spectroscopy, we show that the excess electron initially absorbs in the far-infrared at a frequency for which accompanying ab initio molecular dynamics simulations estimate an initial delocalization length of ≈ 40 Å. The electron subsequently shrinks due to solvation and thereby leaves the terahertz observation window very quickly, within ≈ 200 fs.
Keywords: Terahertz Spectroscopy; Molecular Dynamics Simulation; voda; Water; terahertzová spektroskopie; simulace molekulární dynamiky; kvantová teorie; elektrony; Electrons; Quantum Theory